2009
DOI: 10.5194/acp-9-4439-2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal observations of the tertiary ozone maximum

Abstract: Abstract. We present spatio-temporal distributions of the tertiary ozone maximum (TOM), based on GOMOS (Global Ozone Monitoring by Occultation of Stars) ozone measurements in [2002][2003][2004][2005][2006]. The tertiary ozone maximum is typically observed in the high-latitude winter mesosphere at an altitude of ∼72 km. Although the explanation for this phenomenon has been found recently -low concentrations of odd-hydrogen cause the subsequent decrease in odd-oxygen losses -models have had significant deviation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 21 publications
6
39
1
Order By: Relevance
“…Because of the longer chemical lifetime of ozone in the middle mesosphere, transport processes become dominant over local photochemistry at the altitude of the TOP. The altitude and abundance variability of the TOP induced by downward transport of polar air was recently discussed by Sofieva et al (2009) and Smith et al (2009) While transport plays an important role at the altitude of the TOP where the nighttime O 3 lifetime is long, chemistry becomes important around 0.01 hPa, where O 3 lifetime is shorter. Ozone increases correspond to the sudden temperature decreases in the MLT during or right after the SSWs.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the longer chemical lifetime of ozone in the middle mesosphere, transport processes become dominant over local photochemistry at the altitude of the TOP. The altitude and abundance variability of the TOP induced by downward transport of polar air was recently discussed by Sofieva et al (2009) and Smith et al (2009) While transport plays an important role at the altitude of the TOP where the nighttime O 3 lifetime is long, chemistry becomes important around 0.01 hPa, where O 3 lifetime is shorter. Ozone increases correspond to the sudden temperature decreases in the MLT during or right after the SSWs.…”
Section: Discussionmentioning
confidence: 99%
“…The polar regions were not investigated as night (or day) measurements alone cannot provide continuous coverage. Studies of GOMOS measurements of O 3 , NO 2 , and NO 3 in the polar regions can be found, for example, in , Seppälä et al (2007), Tétard et al (2009), andSofieva et al (2009). We analysed the daily time series of O 3 , NO 2 , and NO 3 profiles by fitting the series by a time independent constant term, annual and semi-annual terms, a solar proxy and two QBO proxies.…”
Section: Discussionmentioning
confidence: 99%
“…The annual variation in the NDR is modulated by oscillations of a planetary timescale (Sonnemann et al, 2007). Sofieva et al (2009) reported that during a sudden stratospheric warming event the tertiary ozone maximum can decrease significantly or can even be completely destroyed. Hocke (2017) has shown the loss of the tertiary ozone layer in the polar mesosphere due to the solar proton event in November 2004.…”
Section: Analysis Of the Night-to-day Ratiomentioning
confidence: 99%
“…Sonnemann et al, 2007;Hartogh et al, 2004) also known as the tertiary ozone maximum (e.g. Sofieva et al, 2009;Degenstein et al, 2005;Marsh et al, 2001). Sonnemann et al (2007) reported that the MMM is a phenomenon that occurs at high latitudes close to the polar night terminator at around 72 km altitude during nighttime in winter and extends into middle latitudes with decreasing amplitude.…”
Section: Introductionmentioning
confidence: 99%